PENERAPAN RESTORATIVE JUSTICE TERHADAP ANAK DI BAWAH UMUR: PENERAPAN RESTORATIVE JUSTICE TERHADAP ANAK DI BAWAH UMUR - Nurmala (LPPM UPMI, 2023)
Children who are in conflict with the law are children who are in conflict with the law, children who are victims of criminal acts, and children who are witnesses of criminal acts. Article 1(3) Law No. 11 of 2012, a child in conflict with the law, hereinafter referred to as a child, is a child who is 12 (twelve) years old but not yet 18 (eighteen) years old who is suspected of committing a crime. Children who become victims of crime, hereinafter referred to as child victims, are children under the age of 18 (eighteen) years who experience physical, moral, mental or economic losses caused by a crime. A child who is a witness to a crime, hereinafter referred to as a child witness, is a child who is not yet 18 (eighteen) years old who can provide information for the purposes of investigation, prosecution and examination at a court hearing regarding a criminal case that he has heard, seen and/or experienced Alone.Handling the problem of children who are in conflict with the law does not only focus on their rights. More than just that, it is necessary to apply restorative justice. Restorative justice can be formulated as an idea that responds to the development of the criminal justice system by focusing on the need to involve the community and victims who feel excluded from the mechanisms that work in the existing criminal justice system. In addition, restorative justice can be used as a frame of mind that can be used in responding to a crime for law enforcers. In various principles and models of restorative justice approaches, the process of dialogue between perpetrators and victims is the basic capital and the most important part of the application of this justice. Direct dialogue between perpetrators and victims allows victims to express what they feel, express hopes for the fulfillment of rights and desires from a settlement of criminal cases. Through dialogue, it is hoped that the perpetrators will be moved to self-correct, realize their mistakes and accept responsibility as a consequence of a crime committed with full awareness.